The Effect of FIFA +11 Program on Functional Movement Screen Scores of Junior Soccer Players - Nezam Nemati; Ali Asghar Norasteh; Mohammad Hosein Alizadeh (The Society of Aging and Physical Activity (SAPA), 2017)
Background. Insufficient movement patterns may expose athletes to injury, so it is vital to recognize and rectify these movement patterns. Objectives. The purpose of this study was to assess the fundamental movement patterns and determine the effect of a four-week FIFA+11 program on functional movement screen (FMS) scores of junior soccer players. Methods. A pre-test post-test quasi-experimental design with an intervention and control group was chosen for the present study. The sample consisted of 28 players at the Rasht education system soccer academy. The players first completed the FMS tasks and then were randomly divided into intervention (n=14) and control (n=14) groups. The intervention group then participated in FIFA+11 for four weeks (three times a week) while control group followed their ordinary warm-up program during this period. After four weeks, both groups completed the FMS tasks and the pre-test and post-test results were compared. Results. The results indicated a significant difference in FMS scores in the intervention group between baseline and post-intervention scores (p = 0.001). No significant difference was found in these scores for the control group (p = 0.082). It is showed a significant difference in FMS scores between the intervention and control groups after intervention (p = 0.001). A 57% increase was observed in the number of intervention group players who achieved a score above the injury threshold (14) after four weeks of intervention. A 36% decrease in asymmetry was also observed in the intervention group. Conclusion. It appears that the FIFA+11 program improved the fundamental movement patterns of the junior soccer players. It is suggested that coaches use FIFA+11 to improve the quality of movement of players and encourage them to exercise using correct movement patterns to avert injury.